Comparative Efficacy of Seven Kinds of Chinese Medicine Injections in Acute Lung Injury and Acute Respiratory Distress Syndrome: A Network Meta-analysis of Randomized Controlled Trials - Guo, Jie; Zhu, Jia; Wang, Qian; Wang, Juan; Jia, Yaodan (Frontiers in Pharmacology, 2021)
Background: Chinese medicine injection (CMI) is wildly used in Acute Lung Injury (ALI) and Acute respiratory distress syndrome (ARDS) treatment. However, what kinds of CMIs are more effective in the ALI/ARDS treatment is uncertain. Objectives: Compare the efficacy of different CMIs to identify the optimal one for the therapy of ARDS patients. Data sources: We searched the data up to 30 April 2020 from MEDLINE, EMBASE, The Cochrane Library, Web of Science, the China Science Journal Citation Report (VIP database), WanFang and the China National Knowledge Infrastructure (CNKI). Study selection: Randomized Clinical Trials assessed at least one of the following out comes: mortality, Oxygenation Index, length of ICU stay, mechanical ventilation duration, APACHEⅡ score, SOFA score and Murray score, for adult patients of ALI/ADRS. Eligible Studies should also use CMIs as complementary therapies in addition to the standard treatment. Data extraction and synthesis: Two reviewers independently assessed the data. Then, we used a Bayesian random-effects network meta-analysis for data synthesis. Results: twenty-six studies were selected (involved 2073 participants). seven kinds of CMIs were evaluated. Compared with standard treatment, Xuebijing is associated with lower mortality. Tanreqing and Xuebijing have the best effect on improving the Oxygenation Index. Huangqi, Danshen, Tanreqing and Xuebijing can significantly reduce the APACHE II score (Huangqi works better than Xuebijing). Huangqi and Xuebijing have the best effect on reducing mechanical ventilation duration and Murray score, while Xuebijing has the best effect on shortening the length of ICU stay. Conclusions: As adjuvant drugs, Xuebijing, Tanreqing and Huangqi show certain effects on treating ALI/ARDS in different aspect, but more evidence is needed.